Pleural plaques related to “take-home” exposure to asbestos: An international case series - Peretz, Alon (Dove Medical Press, 2009)
CONTEXT: While a large number of studies indicate the risks of high-level exposures to asbestos in the workplace setting, a relatively small number of studies describe the risk of pleural disease related to “take-home” asbestos brought into the household by workers exposed to asbestos. Consequently, the risk of pleural disease in family members of asbestos-exposed workers is likely underappreciated. CASE PRESENTATIONS: Two families of siblings, one in Israel and one in the US, were evaluated because of their significant exposures to asbestos brought into the home by family members with heavy occupational exposures. Two of the four children of an asbestos cement debagger in Petach Tikvah, Israel and two children of a pipe lagger in a naval shipyard near Seattle, Washington, manifested benign pleural disease without parenchymal disease, despite having no occupational exposure to asbestos. DISCUSSION: These cases illustrate that “take-home” asbestos exposure may lead to pleural disease at higher rates than commonly realized. RELEVANCE TO CLINICAL PRACTICE: Providers should recognize that due to the potential for “take-home” exposures, asbestos-related disease in a patient may be a marker for disease in household contacts. Patients with family members heavily exposed to asbestos should be strongly encouraged to quit smoking in an effort to reduce any further carcinogenic exposures. Additionally, workplace control and regulation of asbestos use should be emphasized to protect both workers and their families.